Vancomycin Containing PDLLA and PLGA/β-TCP Inhibit Biofilm Formation but Do Not Stimulate Osteogenic Transformation of Human Mesenchymal Stem Cells - Kankilic, Berna; Bayramli, Erdal; Korkusuz, Petek; Eroglu, Hakan; Sener, Burcin; Mutlu, Pelin; Korkusuz, Feza (Frontiers in Surgery, 2022)
Aims: Chronic osteomyelitis, including implant related prosthetic joint infection is extremely difficult to cure. We developed vancomycin containing release systems from Poly (D, L-lactide) (PDLLA) and poly (D, L-lactide-co-glycolide) (PLGA) composites with beta-tricalcium phosphate (β-TCP) to treat Methicillin Resistant staphylococcus aureus (MRSA) osteomyelitis. We asked whether vancomycin containing PDLLA/β-TCP and PLGA/β-TCP composites will prevent early biofilm formation, allow cell proliferation, osteogenic differentiation and stimulate osteogenic signaling molecules in the absence of osteogenic medium. Methods: Composites were produced and characterized with scanning electron microscopy. In vitro vancomycin release was assessed for six weeks. Biofilm prevention was calculated by crystal violet staining. Human bone marrow derived mesenchymal stem cells (hBM-MSCs) and osteosarcoma cells (SaOS-2) proliferation and differentiation were assessed with water soluble tetrazolium salt (WST) and alkaline phosphatase (ALP) staining. Real time quantitative polymerase chain reaction (RT-qPCR) defined osteogenic signaling molecules for hBM-MSCs. Results: Totally 3.1± 0.2 mg and 3.4± 0.4 mg vancomycin released from PDLLA/β-TCP and the PLGA/β-TCP composites, respectively and inhibited early biofilm formation. hBM-MSCs and SaOS-2 cells proliferated on the composites and stimulated ALP activity of cells. Runt-related transcription factor 2 (RUNX2) and SRY-Box transcription Factor 9 (SOX9) expressions were however lower with composites when compared to control. Conclusion: Vancomycin containing PDLLA/β-TCP and PLGA/β-TCP composites inhibited early biofilm formation, proliferated and differentiated hBM-MSCs and SaOS-2 cells but osteogenesis related RUNX2 and SOX9 transcription factors were not strongly expressed in the absence of an osteogenic medium for 14 days.